Quality of life after coronary artery bypass surgery: a pilot study - Diakomopoulou, Eleni; Pistolas, Dimitrios; Papagiannaki, Vasileia; Argiriou, M; Apostolakis, Efstratios; Ouzounidou, A; Merkouris, Anastasios (My University, 2002)
Aim: The aim of this study is to compare the quality of life of coronary artery bypass graft patients before and after the operation. This is a pilot project of a greater research effort whose main aim is to assess the quality of life of those patients over different times after the operation and also to explore the ability of preoperative variables to predict improved outcome. Material - Method: The collection of data was based on interviews with patients before and 4 months after the operation by using the MacNew Heart disease health-related quality of life questionnaire. The study sample consisted of 30 patients (25 men, 5 women) with mean age of 64.8 years (SD=8.54) and average length of stay 15.5 days (SD=5.78). The most frequent risk factors were the lack of exercise (90%) and smoking (66.7%) History of cardiovascular disease was reported by 11 patients (36.7%). Results: There was a significant improvement of the physical (+3.46 - P<0.05) and social (+2.71 - P<0.05) state of the patients after the operation. The emotional state of the patients showed a very small improvement (+0.50 - P=0,16) and the cognitive ability, as it was measured by three questions, showed a decline (0.93 - P<0.001). The internal consistency reliability of the questionnaire ranged from 0.83 to 0.92 for the physical, emotional and social subscales. Conclusions: The results to great degree show that coronary artery bypass surgery enhances the physical and social function of the patients 4 months after the operation but there is a significant need to further explore the effect on the emotional and cognitive state of the patients as well as the possible associated factors.